Analysis of laser and inkjet prints using spectroscopic methods for forensic identification of questioned documents - Gál, Lukáš; Belovičová, Michaela; Oravec, Michal; Palková, Miroslava; Čeppan, Michal (Univerzita Pardubice, 2013)
The spectral properties in UV-VIS-NIR and IR regions of laser and inkjet prints were studied for the purposes of forensic analysis of documents. The procedures of measurements and processing of spectra of printed documents using fibre optics reflectance spectroscopy in UV-VIS and NIR region, FTIR-ATR with diamond/ZnSe and germanium crystals were optimized. It was found that the shapes of spectra of various black laser jet prints and inkjet prints generally differ in the spectral regions UV-VIS-NIR and IR. However, the resolution of individual spectra, and hence of individual printers, based on the simple visual comparison is not reliable enough. However, using of these spectra for identification of individual printers should be enhanced by computational chemometric methods.
Keywords: document; spectroscopy; laser; inkjet